THE TRANSFORMATION OF UINSU STUDENTS’ JOURNALISTIC PRACTICES IN THE ARTIFICIAL INTELLIGENCE ERA TOWARD GOLDEN INDONESIA 2045 - Ahmad Fadil Hsb; M.Yoserizal Saragih (Journal Analytica Islamica, 2026)
The rapid advancement of Artificial Intelligence (AI) has fundamentally reshaped journalistic practices globally, yet its implications within Islamic higher education contexts remain insufficiently explored in academic literature. This study investigates the transformation of journalistic practices among students of the Communication Studies Program at Universitas Islam Negeri Sumatera Utara (UINSU) in the AI era, with particular attention to the interplay between AI literacy, Islamic journalistic ethics, and human resource readiness toward the Indonesia Emas 2045 vision. Employing a qualitative descriptive approach, data were gathered through in-depth interviews with fifteen purposively selected informants, complemented by observation and documentation. Data analysis followed Miles and Huberman's (1994) interactive model, with source triangulation applied to ensure validity. Findings demonstrate that AI has permeated all stages of student journalistic practice, from ideation and information gathering to manuscript editing and digital content distribution. While AI adoption enhances efficiency, productivity, and creative exploration, it simultaneously poses critical challenges, including technological dependency, insufficient fact-checking, algorithmic bias, digital plagiarism, and the erosion of critical thinking and journalistic ethics. AI literacy emerged as the most significant determinant of responsible technology use, while Islamic values of truthfulness (shidq), justice ('adl), and trustworthiness (amanah) serve as essential moral anchors in navigating AI integration. This study contributes theoretically by extending technological determinism theory within an Islamic journalistic education context and practically by proposing an AI-integrated journalistic curriculum model for Islamic universities aligned with the Indonesia Emas 2045 national development agenda.